2006
DOI: 10.1063/1.2165573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bias potential upon H− density near a plasma grid of a negative ion source

Abstract: A molybdenum plasma grid was installed in a 30-cm-long 16-cm-diam 16-pole magnetic multicusp ion source to simulate the effect of a plasma electrode bias of a negative ion source. Effects caused by the bias voltage applied to the electrode upon the plasma parameters, the density of negative hydrogen ions (H−), and the drift velocity of plasma perturbed by the photodetachment of H− were investigated with the direct current laser photodetachment method. The electron density at the distance of 0.5 cm from the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this region, gradients due to plasma sheath and the presence of a magnetic filter create forces strongly affecting the free flight and collisional events. In fact, experiments [153,154] have shown that PG bias and magnetic filter have an important role for the enhancement of H production (trough the electron temperature and density) and extraction. The spatial structure of plasma parameters near the PG is a key point in the transport of negative ions.…”
Section: Plasma-gas Coupling In the Extraction Regionmentioning
confidence: 99%
“…In this region, gradients due to plasma sheath and the presence of a magnetic filter create forces strongly affecting the free flight and collisional events. In fact, experiments [153,154] have shown that PG bias and magnetic filter have an important role for the enhancement of H production (trough the electron temperature and density) and extraction. The spatial structure of plasma parameters near the PG is a key point in the transport of negative ions.…”
Section: Plasma-gas Coupling In the Extraction Regionmentioning
confidence: 99%
“…For the V b at which the I H − takes the maximum intensity, the plasma potential shows a flat spatial distribution against the distance from the plasma electrode. Consequently, the H − ions produced in the driver region upstream of the filter magnetic field [9] can travel to extractor without electrostatic trap [10]. The plasma potential distribution can be more sensitively affect the H − ion transport against the change of V b in H − rich plasmas like the case of cesium seeded ion source comparing with the case of pure H 2 discharge [11].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies on the H − ion transport near the PE in the extraction region of the H − sources [10][11][12][13] have revealed the existence of enhanced transport of H − ions toward the extractor correlated to the plasma electrode bias. This is the physical reason for the enhancement of the n − fraction in the extraction region when the PE is biased positive.…”
Section: Particle Balance In the Extraction Regionmentioning
confidence: 99%